Comparative study of base-isolated irregular RC structures subjected to pulse-like ground motions with low and high PGA/PGV ratios. (June 2021) - Habib, Ahed; AL Houri, Ausamah; Yildirim, Umut
Abstract: Nowadays, vertically irregular reinforced concrete structures are very commonly seen in modern urban construction. These structures are of high vulnerability to lateral seismic shaking intensities as compared to regular buildings due to their inconsistent stiffness distribution along with the height. In general, the utilization of a base isolation system in a reinforced concrete building is considered an effective solution for seismic mitigation in earthquake-prone countries. The behavior of these buildings in both regular and irregular cases has been extensively studied in the literature. Moreover, the performance of the base isolated buildings under pulse-like earthquakes has attracted several researchers through the previous years due to the significant influence of such ground motions on the displacement stability of the isolation system. Currently, the literature is missing a study that evaluates and compares the full nonlinear time history behavior of different irregular reinforced concrete structures under near-fault pulse-like ground motions. Therefore, this study is intended to investigate the time history behavior of various base isolated reinforced concrete models subjected to pulse-like earthquakes with low and high PGA/PGV ratios. As a part of the study, the responses of heavy-story, soft-story, and stepped structures will be compared to the ones of a regular model. Furthermore, the effects of three different isolator's effective damping ratios on the time history responses will be evaluated. The results of the study showed that the behavior of the isolator is influenced by the building irregularity type and the PGA/PGV ratio significantly.